Fresno County Bar Association Annual Bar Banquet at TorNino's - Watkins, Howard::::::::: (1985)
1985 Fresno County Bar Association President Donald Fischbach presenting plaque to Judy Soley for her prior service on the Fresno County Bar Association Board of Directors Judy Soley became the 1986 Fresno County Bar Association President; Howard Zidenberg on far left